PARTICIPATION OF THE PEOPLE IN THE SUSTAINABLE LOCAL DEVELOPMENT OF BANGKOK - Benjathikul Chairungruang, Duangrit (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to Factors Affecting Public Participation in Sustainable Local Development of Bangkok This was Mixed method research. Quantitative the population consisted of people in Bangkok, 6 districts, population of 628, 250 people. Using Taro Yamane sample size calculation method, 340 people were randomly sampled. Use questionnaires as a tool for the confidence value. Reliability was obtained with an alpha coefficient of 0.96. The analysis of the data was used statistics, percentage, mean, standard deviation. And multiple regression Qualitative, in-depth interviews, and 16 key informants. Analyzing and presenting descriptive results. The results of the research were found that the factors affecting the public participation 1) Local development planning 2) Local development activities, 3) Public relations for people to have knowledge and understanding about local development, 4) decision - making to set up local development action plans, and 5) monitoring and evaluating local development performance significantly. Statistics at the .05 level, with the participation of people in the overall sustainable development of the Bangkok local area at a high level. The input from the interviews corroborated the most important issue of participation, namely the involvement of the public in planning local development. It will allow people to play a part in determining the direction for their own community development. And some issues commented on factors that have different effects on people to participate in monitoring and evaluating the performance of local development work By finding incentives Cultivate good values to invite people to participate.